Bei Bei goes home : a panda story - Bardoe, Cheryl, 1971- (Smithsonian kids., 2021)
"Two nations and a mother panda work together to nurture a 'precious treasure' in the remarkable true story of a celebrity panda cub and his life at the Smithsonian National Zoo - and beyond"--